Exploring undergraduate students awareness of internal Shariah auditing in Malaysia - Abdelhakeem Khalid Ahmed, Azam (Tanjong Malim, 2018)
Exploring undergraduate students awareness of internal Shariah auditing in Malaysia by Abdelhakeem Khalid Ahmed, Azam